2016
DOI: 10.1016/j.ijbiomac.2016.01.070
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroxy cinnamic acid as mushroom preservation: Anti-tyrosinase activity kinetics and application

Abstract: Tyrosinase is a key enzyme in post-harvest browning of fruit and vegetable. To control and inhibit its activity is the most effective method for delaying the browning and extend the shelf life. In this paper, the inhibitory kinetics of 4-hydroxy cinnamic acid on mushroom tyrosinase was investigated using the kinetics method of substrate reaction. The results showed that the inhibition of tyrosinase by 4-hydroxy cinnamic acid was a slow, reversible reaction with fractional remaining activity. The microscopic ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…This activity might be attributed to the high level of phenolics in addition to lignans which are distributed in the fruits as well as in the leaves, but in significantly lower amounts. Similar results are reported by Hu et al 58 and Azhar-Ul-Haq et al 59 who found that phenolics and lignans have strong antityrosinase effects. Hydroxyl groups in the phenolics may directly interact with active sites of these enzymes.…”
Section: In Vitro Enzyme Inhibitory Properties Of S Chinensis Extracsupporting
confidence: 90%
“…This activity might be attributed to the high level of phenolics in addition to lignans which are distributed in the fruits as well as in the leaves, but in significantly lower amounts. Similar results are reported by Hu et al 58 and Azhar-Ul-Haq et al 59 who found that phenolics and lignans have strong antityrosinase effects. Hydroxyl groups in the phenolics may directly interact with active sites of these enzymes.…”
Section: In Vitro Enzyme Inhibitory Properties Of S Chinensis Extracsupporting
confidence: 90%
“…Asn205 was suggested to be crucial for tyrosinase activity through the activation of a conserved water molecule 35 46 . The interaction of Asn205 with HQ might prevent this activation, and thus inhibit tyrosinase activity 18 47 48 . Furthermore, in the structures of TyrBm with KA at the entrance of the active site this interaction was also found to be important for KA stabilization 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The most common hydroxycinnamates are p -coumaric, caffeic and ferulic acids. So far, p -hydroxybenzoic acid, chlorogenic acid (the ester of caffeic acid ), vanilic acid (4-hydroxy-3-methoxybenzoic acid) and protocatechuic acid (a dihydroxybenzoic acid) from Hypericum laricifolium Juss 154 , protocatechualdehyde (IC 50 = 0.40 µg/mL) from Phellinus linteus 175 , benzoic acid propyl gallate 309 , orsellinic acid (2,4-dihydroxy-6-methylbenzoic acid) and orsellinates (2,4-dihydroxy-6-methyl benzoates) 310 , p -coumaric acid from ginseng leaves 311 , m -coumaric acid 312 , p -coumarate 313 and its derivatives from leaves of Breynia officinalis 184 caffeic acid and its n -nonyl ester 314 , ferulic acid from Spiranthes sinensis 224 , 4-Hydroxy cinnamic acid 315 , synthetic hydroxycinnamoyl phenylalanyl/prolyl hydroxamic acid derivatives 316 , and seven hydroxycinnamoyl derivatives in green coffee beans 317 have been investigated for their tyrosinase inhibition activity. Among these, propyl gallate is a reversible and mixed-type inhibitor on diphenolase activity of tyrosinase with K IS = 2.135 mM and K i = 0.661 mM 309 .…”
Section: Inhibitors From Natural Semisynthetic and Synthetic Sourcesmentioning
confidence: 99%